2003
DOI: 10.1021/bi0271594
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Engineering Uphill Electron Transfer into the Methylamine Dehydrogenase−Amicyanin−Cytochrome c-551i Complex

Abstract: Within the methylamine dehydrogenase-amicyanin-cytochrome c-551i complex, electrons are transferred from tryptophan tryptophylquinone (TTQ) to heme via the type I copper center of amicyanin. Mutation of Pro94 of amicyanin to Phe increases the redox potential of the copper center within the protein complex by approximately 195 mV. This introduces a large energy barrier for the second electron transfer (ET) step in this three-protein ET chain. As a consequence of this mutation, the ET rate from TTQ to copper exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
3
8
0
Order By: Relevance
“…Essentially the same values of λ and H AB were obtained from each analysis. Furthermore, alteration of ΔG o by site directed mutagenesis of amicyanin caused changes in k ET which were consistent with the predictions of ET theory (33). It is likely that the large magnitude of λ is more a consequence of the TTQ cofactor of MADH than of the copper center of amicyanin (34).…”
Section: Discussionsupporting
confidence: 82%
“…Essentially the same values of λ and H AB were obtained from each analysis. Furthermore, alteration of ΔG o by site directed mutagenesis of amicyanin caused changes in k ET which were consistent with the predictions of ET theory (33). It is likely that the large magnitude of λ is more a consequence of the TTQ cofactor of MADH than of the copper center of amicyanin (34).…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies of the ET reactions of native (16) and P94F (18) amicyanin with MADH and cytochrome c-551i established the validity of this ternary protein complex as a system for analysis of ET reaction rates by ET theory (eqs 4 and 5). It was demonstrated that the changes in ∆G°caused by the P94F mutation yielded predictable changes in k ET values that were consistent with true nonadiabatic ET reactions to and from the copper center.…”
Section: Resultsmentioning
confidence: 96%
“…Electron Transfer Reactions of P94A Amicyanin. The rates of the ET reactions from O-quinol MADH to oxidized P94A amicyanin and from reduced P94A amicyanin to oxidized cytochrome c-551i were determined as described previously for study of the analogous reactions of P94F amicyanin (18). An On-Line Instruments (OLIS, Bogart, GA) RSM16 stopped-flow rapid scanning spectrophotometer was used for kinetic measurements.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations